The clinical efficacy of pure-grind acellular dermal matrix without gelatin in lower extremity skin defect treatment: A prospective randomized study - Kim, Min Ji; Jeong, Yon Soo; Kim, Tae Wook; Park, Dong Ha; Lee, Il Jae (Frontiers in Materials, 2022)
Background: Acellular dermal matrix (ADM) is currently considered as a replacement for lost extracellular matrix. Trials have been conducted on dressing materials with high contents of ADM without any impurities, such as gelatin, which only undergo the grinding process. In this study, we aimed to investigate the clinical application and wound healing effect of pure-grind ADM in lower extremity skin defect treatment. Methods: Patients with skin defects in the lower extremities who did not achieve wound healing within 4 weeks with conservative treatment were enrolled in this study from March 2021 to July 2021. We randomized the patients into two groups. The patients in the experimental group were treated with pure-grind ADM and conventional negative-pressure wound therapy (NPWT), whereas the patients in the control group were only treated with NPWT. Every wound was followed-up for 7 weeks, and complete wound healing was confirmed when the skin defect was fully covered with epithelized tissue. Results: A total of 41 patients were enrolled in this study. Complete wound healing was observed in 73.2% of patients, and 26.8% had an unhealed status until the end of the follow-up. The pure-grind ADM did not promote complete healing (p=0.796) and was not associated with epithelization time but promoted the velocity of epithelization (experimental 5.58 vs. 3.50 cm2/day, p=0.020). Considering the time of healing, the decrease in wound depth was more extensive (p=0.021), the speed of granulation tissue formation was higher, and this difference was more evident after 5 weeks of treatment in the experimental group. Conclusion: We demonstrated the clinical efficacy of pure-grind ADM in treatment of lower extremity skin defects. This new type of ADM, without any impurities, is important in wound healing. Its depth filling effect is powerful, and it can promote epithelization velocity and speed of granulation tissue formation.